A Study Of The Factors Influencing The Location Selection Decisions Of Information Technology Firms - Rajkumar, Paulrajan (Asian Academy of Management (AAM), 2013)
This study seeks to understand the factors influencing the location selection decision making of information technology companies in India. The development of industrial estates has experienced phenomenal growth due to the globalisation policy of the government of India. Seven constructs, which include manpower, technology, social, hedonistic, industrial site, economic governmental factors, and as well as their underlying items, play vital roles in location selection decisions. A pilot study was conducted to understand the market and frame an effective questionnaire. The survey used a structured questionnaire for personnel from information technology organisations, government, and support service organisations. The data collected from the respondents was analysed to reduce it to meaningful factors. The factorised data and the constructs were further analysed with the help of a structural equation model. These analyses and path diagram reveal new dimensions in the location decision-making process.